Epistimologi Sarung sebagai Identitas dan Simbol Pendidikan Karakter di Pondok Pesantren Mambaul Ulum Bata-Bata Pamekasan - Syakir, Ahmad Fauzan; Qomaruzzaman, Ahmad; Ahsani, Abdurrohman Nur (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2023)
The santri each have their own distinct identity thanks to the sarong. In addition, at the Mambaul Ulum Bata-Bata Pamekasan Islamic boarding school, the sarong is one of the media, a means of preserving and developing character education that always preserves Islamic culture and religious souls.With a material culture perspective as a concept of local culture and national heritage, "Sarong" also has non-material values like symbols of students, social class, kindness, and honor.Sarongs of varying sizes, colors, and designs influence people, society, and even national identity.The sarong has even become a part of Indonesian religion's diversity and a symbol.Truly zeroing in on and developing a sarong culture should be viewed as a work to keep up with and encourage the educating of individuals, so there will be a balance of disciplinary culture in completing their exercises as residents and understudies specifically.As a result, this paper employs a strategy or point of view:the idea of Material Culture, the perspective of social classes, and the integration of character education.This article's writing method is a literature review and content analysis of various sources.The study's findings demonstrate that, in an Islamic boarding school setting with strong historical significance, the sarong can function as a symbol of character education and identity.